Evaluasi Kinerja Guru SD di Kabupaten Tabalong Menggunakan Metode Kuantitatif - Susanty, Susanty; Aslamiah, Aslamiah; Norhapizah, Norhapizah; Novitawati, Novitawati (Green Publisher Indonesia, 2025)
Teacher performance is a crucial element in the quality of education, influenced by various factors such as leadership style, work environment, organizational citizenship behavior (OCB), interpersonal communication, and organizational commitment. These factors can interact and affect how teachers carry out their duties in the educational environment. However, the limited research that simultaneously evaluates the impact of these factors on teacher performance in a single region serves as an important basis for this study. The aim of this study is to comprehensively evaluate how leadership style, work environment, organizational citizenship behavior, interpersonal communication, and organizational commitment affect teacher performance. The novelty of this research lies in the integration of these factors into a single analysis, providing a broader understanding of teacher performance in Tabalong District. This study employs a quantitative approach with regression analysis to test the existing hypotheses. The results show that all the factors tested have a significant effect on teacher performance, with organizational commitment playing an important role in improving performance. These findings suggest that improving these factors can enhance educational quality through the improvement of teacher performance. In conclusion, this study emphasizes that to improve the quality of education, it is essential to address and strengthen the factors influencing teacher performance, particularly by enhancing organizational commitment, which has been shown to significantly impact teacher performance.